Severe outcomes among adults with TB during COVID-19 - T. Jacobs; E. Morden; M. Smith; A. von Delft; R. Kassanjee; V. Mudaly; A. Boulle; M-A. Davies (IJTLD Open)
BACKGROUND: The COVID-19 pandemic prompted strict public health measures to reduce SARS-CoV-2 transmission, potentially interrupting TB programmes in the Western Cape, South Africa. METHODS: We conducted a retrospective cohort study, estimating changes in new TB case rates and risk of death during TB-specific admissions within 6 months of TB first evidence, during the pre-pandemic (1 January 2019–26 March 2020) and after the implementation of public health and social measures (PHSM) periods (26 March 2020–30 September 2021), based on PHSM strictness. We used interrupted time series and logistic regression models to adjust for key characteristics. RESULTS: We found an average 22% reduction (95% CI 19–25) in monthly TB cases during the entire PHSM implementation period. Additionally, the risk of death during TB-specific admissions increased, with the adjusted odds ratio ranging across PHSM levels from 1.36 (95% CI 1.17–1.57) on Level 1 to 1.44 (95% CI 1.16–1.79) on Level 2 compared with the pre-pandemic period. CONCLUSIONS: There was a decline in the number of diagnosed TB cases and an increased risk of severe outcomes from 26 March 2020 to 30 September 2021 in the Western Cape. TB programme recovery strategies must be prioritised, and TB management programmes must be integrated into future pandemic responses.